One land and three narratives: Palestinian sites of memory in Israel. (July 2018) - Assmann, Aleida
The first part of the article invites a fresh look at the often defined concepts of 'space' and 'place', connecting them to different subject positions, mental frames and projects. The second part addresses memory issues that underlie the political conflict between the state of Israel and Palestinians in the Near East. It will analyse two seemingly incompatible memories related to the same events and topography. The focus of the essay is not only on the divisive force with which two incompatible histories are constructed in the same landscape but also on recent memory practices and performances that raise awareness of this impasse and work towards a more complex and inclusive transnational memory of the entangled history of 1948.